Case Report: Fish bone-induced duodenal perforation leading to bile duct stones and portal vein thrombosis - Shi, Yuyi; Xu, Xiliang; Wang, Yuxu; Qu, Wenhao (Frontiers in Medicine, 2025)
We present a case of duodenal perforation caused by accidental ingestion of a fishbone, presenting with right upper abdominal pain and jaundice. Imaging studies revealed duodenal perforation, common bile duct stones, and portal vein thrombosis. By reviewing the patient’s clinical presentation, diagnostic process, treatment measures, and prognosis, we analyzed the potential mechanisms underlying this complex pathological condition and proposed appropriate clinical management strategies. Duodenal perforation caused by foreign bodies is a rare but potentially fatal condition that may lead to severe complications. Foreign body-induced duodenal and bile duct perforation can act as potential triggers for common bile duct stones and portal vein thrombosis. Its intricate pathophysiology requires heightened vigilance and comprehensive evaluation. Prompt diagnosis and individualized treatment strategies are critical for improving patient outcomes.